ArchiMed: A Medical Information and Retrieval System - Dorda, W.; Wrba, Th.; Duftschmid, G.; Sachs, P.; Gall, W.; Rehnelt, Ch.; Boldt, G.; Premauer, W. (Methods of Information in Medicine, 1999)
ArchiMed is a highly flexible medical data storage and retrieval system which adds sophisticated clinical research support to a standard hospital information system (HIS).Currently, the HIS of Vienna General Hospital-University Hospital (2000 beds) stores the clinical data of over 2 million patients. While this system supports patient care (e.g., ADT, clinical chemistry, diagnosis, procedures), it has no features to facilitate research, such as the management of clinical studies.ArchiMed is designed to support clinical research. It includes an independent database, which mirrors virtually all the information held in the HIS while also allowing new data to be collected independently and to be added to the database. Flexible retrieval and analysis of data contained in the database are then possible. Thus, existing patient data can be smoothly incorporated into a study together with data collected specifically for research purposes. The system has already been successfully installed in the departments of surgery and soon in other departments as well.
Keywords: Clinical Information System; Data Retrieval System; Object Orientation; Semi-automated Database Design